Immunohistochemical Expression of Epidermal Growth Factor Receptor in Human colorectal Adenocarcinoma (A clinicopathological study) - AbdulGhafour, Kifah h.; Al- khafaji, Khitam R.; Al-Atroushi, Sazan A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Colorectal Adenocarcinoma contributes one of the most common malignancies and the second leading cause of death from cancer in the western world. Epidermal growth factor receptor (EGFR) belongs to a family (ErbB-tyrosine receptors), EGFR plays an important role in the pathogenesis of colorectal cancer. Objectives: to evaluate the immunohistochemical expression of epidermal growth factor receptors (EGFR) in colorectal adenocarcinoma and to correlate this expression with different clinicopathological parameters. Pateints and method: In this study clinicopathological parameters of twenty five colorectal adenocarcinoma cases diagnosed in private pathology laboratories in Baghdad /Iraq from November 2012 to September 2013 were respectively evaluated in terms of age, gender, pathological diagnosis including; tumor location, lymph node status. EGFR expression was investigated immunohistochemically. Results: twenty five colorectal cancer patients were included in this study with median age 54.5, range from (28-81)years, 15 cases (60%) were female and 10 (40%) cases were male. Tumor size range from 3-10 cm with mean 6.5 cm, 10 (40%) cases were from rectum, 7 (28%) from the right side colon & 8 (32%) cases were from from left side colon. Twenty three (92%) cases were moderately differentiated, and two (8%) cases were poorly differentiated, five (20%) cases were T1, 10 (40%) cases were T2, 5 (20%) cases were each T3 & T4 respectively. 3 (12%) cases were N1, 7 (28%) cases were N2, and fifteen (60%) cases have no lymph node involvement. Three (12%) cases with distant metastasis. Eighteen (72%) cases of colorectal adenocarcinoma demonstrate EGFR reactivity in > 1% of the tumor cells. No significant statistical correlation was noticed between EGFR expression and each of age, gender, site of the tumor and grade of tumor (P value > 0.05). A significant statistical correlation was noted between EGFR expression and local tumor invasion (T) and lymph node involvement (p value <0.05). Conclusion: Epidermal growth factor receptor plays an important role in colorectal adenocarcinoma oncogenesis. EGFR expression appears to have a value as a prognostic biomarker, since it’s expression by the tumor cells is significantly correlated to lymph node involvement and tumor local invasion.